OTUB1 Promotes Progression and Proliferation of Prostate Cancer via Deubiquitinating and Stabling Cyclin E1 - Liao, Yihao; Wu, Ning; Wang, Keke; Wang, Miaomiao; Wang, Youzhi; Gao, Jie; Zhong, Boqiang; Ma, Fuling; Wu, Yudong; Jiang, Ning (Frontiers in Cell and Developmental Biology, 2021)
Background: Prostate cancer (PCa) is currently the most common and highest incidence of cancer in men all over the world. OTUB1 has been reported to be a critical role in various kinds of cancers, closely related with proliferation, migration and clinical prognosis. The aim of this research was to investigate the influence of OTUB1 in PCa, and to identify the mechanism underlying function. Methods: Using TCGA database, we identified OTUB1 higher expression in PCa. We observed the changes of functional behavior in PC3 and C4-2 cells through overexpression or knock down of OTUB1. Subcutaneous ectopic tumors were conducted and IHC of tumors tissue in nude mice also carried out. Western blotting and co-immunoprecipitations assays were conducted to identify that OTUB1 interacted with cyclin E1. Results: We found that the expression of OTUB1 was significant higher in PCa than in Benign prostatic hyperplasia (BPH). The overexpression of OTUB1 promoted obviously proliferation and migration in PC3 and C4-2 cells via regulating Cyclin E1 protein stability, and contrary observation in OTUB1 knock down. The nude mice experiment further explained our conclusions. We finally identified that OTUB1 promoted the progression of PCa by deubiquitinating and stabling cyclin E1. Conclusions: Our findings reveal the important role of OTUB1 in PCa, OTUB1 promoted cyclin E1 protein stability in PCa. Knock down of OTUB1 can significantly repressed development of cancer. OTUB1 might serve a newly and potential therapy target for PCa.